Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 11 - Section 11.2 - Solving Quadratic Equations by Completing the Square - Exercise Set - Page 776: 23



Work Step by Step

$x^{2}+6x+13=0$ Use the quadratic formula to solve this equation. The formula is $x=\dfrac{-b\pm\sqrt{b^{2}-4ac}}{2a}$. Here, $a=1$, $b=6$ and $c=13$ Substitute: $x=\dfrac{-6\pm\sqrt{6^{2}-4(1)(13)}}{2(1)}=\dfrac{-6\pm\sqrt{36-52}}{2}=...$ $...=\dfrac{-6\pm\sqrt{-16}}{2}=\dfrac{-6\pm4i}{2}=-3\pm2i$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.